2016
DOI: 10.28945/3534
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Use of Twitter in Developing Countries: Integrating Innovation Attributes, Uses and Gratifications, and Trust Approaches

Abstract: Based on the diffusion of innovation (DOI) theory (Rogers, 2003), the uses and gratifications (U&G) theory, and trust theory, this study investigated the factors that influence the use of Twitter among the Kuwaiti community. The study surveyed Twitter users in Kuwait. A structured online questionnaire was used to collect data, and 463 respondents who provided complete answers participated. Multiple regression analysis was used to examine the effect of three theoretical perspectives on Twitter usage. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 64 publications
(84 reference statements)
2
15
0
Order By: Relevance
“…Thus, users' perceptions about the informativeness of a system represent a major antecedent to the acceptance and use of that system. Alajmi et al (2016) found the need for information was a key and significant predictor of Twitter use. Thus, ERP informativeness can be defined as the extent to which an ERP system provides its users with the information they need to complete their job activities.…”
Section: Informativenessmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, users' perceptions about the informativeness of a system represent a major antecedent to the acceptance and use of that system. Alajmi et al (2016) found the need for information was a key and significant predictor of Twitter use. Thus, ERP informativeness can be defined as the extent to which an ERP system provides its users with the information they need to complete their job activities.…”
Section: Informativenessmentioning
confidence: 97%
“…According to UGT, consumers actively evaluate the available media and they select the media or innovation that they believe will satisfy their needs and maximize their gratification. The UGT regards individuals as agents who perform different actions based on the needs that they expect to satisfy from using a certain medium (Alajmi et al, 2016). In other words, UGT focuses on the motives for specific types of usage, and the satisfaction individuals obtain from such use.…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%
See 3 more Smart Citations